FREE SEX BEHAVIOR IN TEENAGE SMA NEGRI 2 LELES GARUT - Sukma Senjaya (LPPM Universitas Bakti Tunas Husada, 2018)
The increasing free sex culture among students began to threaten the future of the Indonesian nation. Even free sex behavior is increasing from year to year. The data collected by the Director of Youth and Protection of Reproductive Rights of the National Family Planning Coordinating Board (BKKBN), Masri Muadz, shows that the case shows an increasingly saddle for us. The goal to be achieved in this research is to identify the knowledge, attitudes and actions of respondents about free Sex Behavior in adolescents in SMA Negri 2 Leles. This research uses descriptive research design. Descriptive is a research method that is done with the main purpose to create a description or description of a situation objectively (Notoatmodjo, 2005). Where this research to know the description of sexual behavior of adolescent in SMA Negri 2 Leles. The sample used is 100 respondents consisting of grade 1, class 2, and grade 3 with inclusion criteria registered as a student of SMA Negri 2 Leles. Instruments used in the form of questionnaires knowledge, attitudes and actions of students related to free sex behavior in adolescents. The questionnaire was modified again by researchers from previous researchers.Conclusions from the study: Free sex is a sexual relationship conducted with people based on likes like, ranging from kissing (kiss the forehead, cheeks, and lips) to stimulate the holding of the genitals and sexual intercourse. Teenagers have free sex because of internal and external factors. The various reasons and factors of teenagers to have free sex are teenagers have a wrong view of the meaning of love, easy to get emotion and persuasion couples or peers based on the mistaken love, so it is easy to have free sex. Besides that the influence of social media about sex that smells porn easy and easily accessed flowing freely. The teenagers are now not only in the city even in the village has experienced a shift in value that is quite worrying about sex and romance, many teenagers who do not understand about the problem of sex and adolescent love today. Keywords: Behavior, Free Sex, Adolescent